On the performance of telemedicine system using 17-GHz orthogonally polarized microwave links under the influence of heavy rainfall. - Bernard Fong (IEEE Transactions on information technology in biomedicine)
This paper describes the design of a telemedicine system based on next-generation wireless local area networks (WLANs) operating at 17 GHz. Seventeen gigahertz is proposed for next-generation WLAN services offering numerous advantages over traditional IEEE 802.11 networks that operate in the range of 2.4-5 GHz. Orthogonal polarization is often used to increase spectrum efficiency by utilizing signal paths of horizontal and vertical polarization. Radio waves exceeding 10 GHz are particularly vulnerable to signal degradation under the influence of rain which causes an effective reduction in isolation between polarized signal paths. This paper investigates the influence of heavy rain in a tropical region on wide-band microwave signals at 17 GHz using two links provided by a fixed broad-band wireless access system for two-way data exchange between paramedics attending an accident scene and the hospital via microwave equipment installed in the ambulance. We also study the effects of cross polarization and phase rotation due to persistent heavy rainfall in tropical regions.